2016
DOI: 10.1590/1414-431x20155125
|View full text |Cite
|
Sign up to set email alerts
|

Expression of merlin, NDRG2, ERBB2, and c-MYC in meningiomas: relationship with tumor grade and recurrence

Abstract: Meningiomas are common, usually benign tumors of the central nervous system that have a high rate of post-surgical recurrence or regrowth. We determined expression of the proteins merlin, NDRG2, ERBB2, and c-MYC in meningiomas using immunohistochemistry and assessed relationships between protein expression and gender, age, tumor grade, and recurrence or regrowth. The study sample comprised 60 patients, (44 women and 16 men) with a mean age of 53.2±12.7 years. Tumors were classified as grade I (n=48) or grades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
3
15
1
3
Order By: Relevance
“…Although these studies found a strong relationship between loss of NDRG2 expression and tumor grade/recurrence, a larger study by Ongaratti et al (n = 60) did not observe this effect using immunohistochemistry [67]. The lack of reproducibility could have been caused by the small number of meningiomas with invasive and aggressive characteristics in this study (n = 12 for tumor grades II and III combined), or by the fact that the two studies used different antibodies for immunohistochemistry.…”
Section: Meningiomacontrasting
confidence: 62%
“…Although these studies found a strong relationship between loss of NDRG2 expression and tumor grade/recurrence, a larger study by Ongaratti et al (n = 60) did not observe this effect using immunohistochemistry [67]. The lack of reproducibility could have been caused by the small number of meningiomas with invasive and aggressive characteristics in this study (n = 12 for tumor grades II and III combined), or by the fact that the two studies used different antibodies for immunohistochemistry.…”
Section: Meningiomacontrasting
confidence: 62%
“…Wang et al observed that when the gene expression of HER2 was down-regulated, the proliferative and invasive ability of the meningioma cells were decreased, and these cells had higher rates of apoptosis (24). Moreover, consistent with our results, some studies reported the higher expression of HER2 on the surface of higher grade meningiomas, although they stated no statistical significance for this association (14,15). On the other hand, there are studies that report no correlation between HER2 expression and histological grade and prognosis of meningiomas (17,25), and a few studies have even shown decreased HER2 expression in higher grade meningiomas (3).…”
Section: █ Discussionsupporting
confidence: 85%
“…In addition, Wang et al demonstrated that overexpression of HER2 resulted in meningiomas with increased cell invasion, migration, and proliferation, whereas downregulation of HER2 protein expression inhibited the neoplastic cells' motility and proliferation, which led to an increase in apoptosis and arrest cell cycle at the G0/G1-phase (24). In addition, higher expression of HER2 in higher grades of meningioma (grade II, III) in comparison to low-grade tumors (grade I) has been reported (13,15). On the other hand, there are studies that report no association between HER2 expression and meningioma features (14).…”
mentioning
confidence: 99%
“…Among the 42 overexpressed genes in our study, the majority (23 of 42) are associated with dysregulation of gene expression in one or more human cancers. These include, but are not limited to, FOSB [ 40 ], FOS [ 41 ], BMPR1B [ 42 ], WNT5A [ 43 , 44 ], PDPN [ 45 ], BMPER [ 46 ], IRF6 [ 47 ], and MYC [ 48 , 49 ]. Additionally, FOS, MYC, and PDPN have been shown to be overexpressed specifically in meningeal tumors [ 41 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%